Antimicrobial Interactions during the Fermentation of Cassava Dough into Agbelima - Siaw, M.E. (University of Ghana, 2000)
The microbial bioprocesses, which occur during the fermentation of cassava dough into agbelima cause considerable changes that affect its organoleptic properties, nutritional value and also enhances the microbial safety of the food. Fermentation of cassava dough into agbelima involves activities of different groups of microorganisms, which result in the production of a sour dough with smooth texture. The microorganisms include Bacillus spp. mainly Bacillus subtilis, Yeast –Candida krusei, Candida tropicalis, Zygosaccharomyces spp. and lactic acid bacteria mainly Lactobacillus plantarum, Lactobacillus fermentum and Lactobacillus brevis. The interactions within and between the different types of microorganisms were studied using the Agar Well Diffusion Assay method. Nearly all lactic acid bacteria isolated at the end of agbelima fermentation inhibited those, which were present at the start of fermentation. Three out of 10 isolates of Bacillus spp. tested were inhibited by all 20 isolates of lactic acid bacteria tested but these lactic acid bacteria inhibited none of the yeasts. Three out of 10 Bacillus spp., which was all Bacillus subtilis, inhibited growth of yeasts. Twelve isolates of Lactobacillus plantarum inhibited bacteriocin indicator organisms, namely Lactobacillus sake and Listeria monocytogenes. When supernatants of L. plantarum isolates were neutralized inhibitory effect of the isolates were lost on Lactobacillus sake and Listeria monocytogenes therefore none of the isolates studied tested positive for bacteriocin production. The growth patterns and acid production of some selected Lactobacillus plantarum isolates were also investigated using batch fermentation in a fermentor. The growth pattern of Lactobacillus plantarum isolates (LAB 9, LAB 6, LP 11 and LP 3) corresponded with increases observed in titratable acidity and decreasing pH of the agbelima. Acid production was fastest in Lactobacillus plantarum isolate-LAB 9. In investigating the microbiological safety of cassava dough-agbelima, pure cultures of enteric pathogens: Salmonella typhimurium 9, Salmonella enteritidis 226, Vibrio cholerae C-230, Shigella dysenteriae 2357T and Escherichia coli D2188, were inoculated into four cassava dough systems at a concentration of 6 7 10 -10 cfu per gram of cassava dough. When inoculated into spontaneously fermenting cassava dough there was a decrease in population of all the enteric pathogens from 107 to zero cfu/g after 24h of fermentation. When inoculated into 48h fermented cassava dough (pH 3.85) all the pathogens died after 4-8h. When inoculated into 48h fermented cassava dough, which had been cooked into a semi-stiff porridge the enteric pathogens disappeared between 4-8h. When inoculated into fermenting cassava dough of specific pHs between 4.40 and 3.81 depending on the pH of the dough the pathogens survived for between 2-5h. When the fermented cassava dough was neutralized the inoculated pathogens survived for 24h-48h. The decrease in population of the pathogens in the different systems also corresponds with increases observed in titratable acidity and decreasing pH of the agbelima. This indicates that the acidic condition prevailing in the agbelima is effective in preventing the growth and survival of the pathogens used. Microbial development and succession in the natural ecosystem of agbelima is therefore controlled by complex interactions, which are mainly determined by acid production